Governance and regulations' contemporary issues - Grima, Simon; Marano, Pierpaolo (Contemporary studies in economic and financial analysis ;, 2018)
'Contemporary Issues in Economic and Financial Analysis 99' includes fourteen studies on contemporary issues within governance and regulations by authors invited from various universities and institutions. The chapters are a mix of discussion-based studies and empirical research studies aimed at understanding particular aspects of governance and regulations. Some refer to a particular country - specifically Malta, Indonesia, and India - and others are more generic and/or European-focused. These chapters include studies of the following: the challenges of corporate governance in small family-owned firms; a credit institution's perspective for managing conduct risk in the boardroom; the implications of the regulation and governance of financial advice in Europe for the retail financial advice sector and its consumers; the barriers to the development of Maltese cooperatives; corporate governance and cash holdings in Indian firms; whether good governance fosters trust in the government; the impact of takeover bids on European law and corporate governance; the developments and outcomes of the reform of the doctrine of "utmost good faith" in the UK; whether corporate decisions in Indonesia are a result of corporate governance requirements; earning management and audit reports; the European deposit insurance scheme; product intervention of supervisory authorities in financial services; the teaching of financial services regulation; how to link the human element to the risk management process, which is one of the internal control processes in governance of an organisation; and whether the transparency regime on the financial institutions market really works.